Russian Experience in Transforming Teaching Methods in Legal Disciplines in Course of the COVID-19 Pandemic - Luparev, Evgeniy Borisovich; Potapenko , Sergey Victorovich; Epifanova, Elena Vladimirovna (Medicine, Law & Society, 2021)
The purpose of the present research is to analyze specific features of educational process in legal sphere in course of the COVID-19 pandemic. The research objectives comprise the following issues: firstly, depiction of the initial state of teaching in legal sphere at the beginning of the pandemic; secondly, transformation process of teaching methods taking into account distinguishing features of the Russian legislation in the field of education; thirdly, correlation of administrative restriction practices with academic freedoms on the example of the Russian Federation. One of the results of this study is the conclusion that it is necessary to prioritize the study of the fundamental theory of law in comparison with commenting on the current legislation in order to be able to substantiate the regulation of non-standard situations in the life of society. The principal outcome of the present survey is a consideration that the Russian legislation in the sphere of education that requires implementation of such educational procedures components as training, education, scientific activity and upbringing cannot be completely implemented under conditions of the imposed administrative restrictions in course of the pandemic.